Age‐related changes in immune function (immune senescence) in caries and periodontal diseases: a systematic review - Preshaw, Philip M.; Henne, Karsten; Taylor, John J.; Valentine, Ruth A.; Conrads, Georg (Journal of clinical periodontology, 2017)
Aim To systematically review the evidence regarding immune senescence in the pathogenesis of periodontitis and dental caries. Methods A systematic search of electronic databases utilizing medical subject headings (MeSH terms) supplemented by screening of review articles and other relevant texts was undertaken. Results Seventy‐three articles were included (43 for periodontitis, 30 for caries). Study results were found to be generally heterogeneous. Regarding periodontitis, human studies suggest evidence for altered neutrophil function and increased production of pro‐inflammatory mediators (e.g. interleukin‐1β, interleukin‐6 and prostaglandin E2) in older compared to younger subjects, and animal experiments suggest increased expression of genes that contribute to a pro‐inflammatory state in older compared to younger animals. Regarding dental caries, research relating to changes in immune functioning and the impact of ageing is in its infancy. A small number of studies have reported components of innate and adaptive immunity that affect the composition of saliva and dental biofilms with possible impacts on caries progression. Conclusion There is evidence that immune functioning related to periodontitis and (less investigated) dental caries alters with increasing age. In both conditions, age‐associated mechanistic changes in immune functioning are complex and incompletely understood and it is not clear how these relate to disease susceptibility.